2021
DOI: 10.1088/1361-651x/abfeae
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained molecular dynamics simulation of cis-1,4-polyisoprene with silica nanoparticles under extreme uniaxial tension

Abstract: Coarse-grained (CG) cis-1,4-polyisoprene (PI) models with multiple silica nanoparticles (NPs) are built to study the effect of NPs and crosslinks in the uniaxial tensile simulation. The potential functions of the CG models are obtained mainly via the iterative Boltzmann inversion method. The tensile simulation results show that the grafted silica NPs and the crosslinked structure play reinforcing roles while the smooth silica NPs do the opposite, which have the similar trends with the experiment results. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…The CG model of a silica nanoparticle-impregnated cis -1,4-polyisoprene polymer was built to study the effect of nanoparticles and cross-links in the uniaxial tensile simulation. 121 The results of this study showed that the polymer-grafted silica nanoparticles and the cross-linked structure play reinforcing roles, while the smooth nanoparticles do the opposite, which was in line with the experiment results. Further, the same group investigated the effects of silica/carbon black hybrid nanoparticles on the viscoelastic properties of uncross-linked cis -1,4-polyisoprene rubber.…”
Section: Coarse-grained Models For Polymer–solid Hybrid Systemssupporting
confidence: 89%
See 1 more Smart Citation
“…The CG model of a silica nanoparticle-impregnated cis -1,4-polyisoprene polymer was built to study the effect of nanoparticles and cross-links in the uniaxial tensile simulation. 121 The results of this study showed that the polymer-grafted silica nanoparticles and the cross-linked structure play reinforcing roles, while the smooth nanoparticles do the opposite, which was in line with the experiment results. Further, the same group investigated the effects of silica/carbon black hybrid nanoparticles on the viscoelastic properties of uncross-linked cis -1,4-polyisoprene rubber.…”
Section: Coarse-grained Models For Polymer–solid Hybrid Systemssupporting
confidence: 89%
“…More recently, the IBI approach has been used to generate the CG models of silica nanoparticles in a polymer matrix. The CG model of a silica nanoparticle-impregnated cis -1,4-polyisoprene polymer was built to study the effect of nanoparticles and cross-links in the uniaxial tensile simulation . The results of this study showed that the polymer-grafted silica nanoparticles and the cross-linked structure play reinforcing roles, while the smooth nanoparticles do the opposite, which was in line with the experiment results.…”
Section: Coarse-grained Models For Polymer–solid Hybrid Systemssupporting
confidence: 83%
“…The NP volume fraction had an effect on the stress-strain behavior of the nanocomposite due to the network formed between polymers and nanofillers; in particular, the stress increased with NP volume fraction in the linear elastic regime (at 10% strain), and the higher surfaceto-volume ratio of the NPs was attributed to contribute to the mechanical improvement of the nanocomposite [27]. Moreover, the grafting of NPs with polymers was reported to also reinforce the nanocomposite and increase the elastic constants [28][29][30]. It was also found that strain hardening was only weakly affected by grafting density or NP size [31].…”
Section: Introductionmentioning
confidence: 98%
“…Molecular simulations of PNCs have increased significantly in recent years, as their complexity can now be approached thanks to advances in high-performance computing. Molecular dynamics (MD) and other particle-based mesoscale methods are well suited to explore the behavior of these materials, revealing details that are not readily accessible to experiments. Today, most MD simulation of rubbery PNCs are still carried out with generic coarse-grained models, which aim at simplicity and a general understanding, rather than quantitative, predictive modeling. Despite their greater complexity, in recent years there have been some notable atomistic (i.e., chemically detailed) simulations of silica-filled rubber networks, which in principle may be used to address system-specific questions.…”
Section: Introductionmentioning
confidence: 99%
“…Today, most MD simulation of rubbery PNCs are still carried out with generic coarse-grained models, which aim at simplicity and a general understanding, rather than quantitative, predictive modeling. 33 39 Despite their greater complexity, in recent years there have been some notable atomistic (i.e., chemically detailed) simulations of silica-filled rubber networks, 40 42 which in principle may be used to address system-specific questions.…”
Section: Introductionmentioning
confidence: 99%